Effects of branched-chain volatile fatty acids and fibrolytic enzyme on rumen development in pre- and post-weaned Holstein dairy calves. Issue 6 (11th November 2020) - Liu, Yan-Rong; Wang, Cong; Liu, Qiang; Guo, Gang; Huo, Wen-Jie; Zhang, Yan-Li; Pei, Cai-Xia; Zhang, Shuan-Lin
Abstract: The study evaluated the effects of branched-chain volatile fatty acids (BCVFA) and fibrolytic enzyme (FE) on rumen development in calves. Forty Holstein male calves at the same ages (15 ± 2.5 days of age) and weights (45 ± 3.3 kg of body weight [BW]) were assigned randomly to four groups with a 2 × 2 factorial arrangement of treatments. Supplemental BCVFA (0 g/d or 18 g/d) and FE (0 g/d or 1.83 g/d) were fed to calves. Data were analyzed as a 2 × 2 factorial arrangement random design by the mixed procedure of SAS. The BCVFA × FE interaction was observed for ruminal propionate, blood growth hormone (GH) and insulin-like growth factor-1 (IGF-1), and GH receptor (GHR) and IGF-1 receptor (IGF-1R) expression in the rumen mucosa. Dry matter intake was higher for BCVFA addition. The higher average daily gain and ruminal volatile fatty acids were observed for BCVFA or FE addition. Stomach weight and the length and width of rumen papillae were higher for BCVFA addition. The higher expression of GHR, IGF-1R and 3-hydroxy-3-methylglutaryl-CoA synthase 1 in rumen mucosa, and blood GH and IGF-1 were observed with BCVFA or FE addition. Blood β-hydroxybutyrate and acetoacetate were higher for BCVFA addition. The results indicated that rumen development was promoted by BCVFA, but was not affected with FE addition in calves.